Research on locomotive automatic operation system crossing railway bureaus and route boundaries - LIU Yaofeng; ZHOU Wenwei; ZHANG Zhengfang (机车电传动)
The automatic train operation (ATO) system for HXD1 locomotives has been incorporated in routine operational assessments on the Xi'an-Ankang line under the Xi'an railway bureau. This paper aims to address the challenges posed to the locomotive ATO system in future operational scenarios that involve crossing the railway bureaus and route boundaries. It presents an in-depth analysis of the difficulties faced by the ATO system in these scenarios including operation across multiple railway lines, track and yard transfers, and diverse train formations and vehicle types. The study focuses on the research and implementation of key technologies for operation crossing different bureaus and route boundaries, including electronic maps and operational scales, transfer-oriented operational planning and control, as well as operational planning and control for multiple formations and vehicle types. Field application results demonstrate that these technologies contribute to the safe operation of freight trains in operational scenarios involving different bureaus and route boundaries, by enhancing the adaptability of the locomotive ATO system.